The Impact of the Arts on Children's Cognitive Development - Syafitri, Musdalifah (Journal of Studies on Art, Culture and Society, 2024)
This study investigated the impact of children's engagement in artistic activities on their cognitive development. The research examined three key aspects of cognitive development: critical thinking skills, creativity, and problem-solving abilities. A sample of elementary school students was divided into two groups: one group participated regularly in art-based activities, while the control group did not.The results revealed that children involved in the arts demonstrated significantly higher scores on tests of critical thinking skills, such as the ability to analyze information, draw conclusions, and evaluate arguments, compared to the control group. Additionally, the art-engaged children exhibited greater creativity, as evidenced by higher scores on measures of fluency, flexibility, and originality of ideas. Furthermore, the data analysis indicated that the art-involved children had better problem-solving skills, displaying enhanced abilities in identifying problems, generating alternative solutions, and evaluating outcomes.These findings provide empirical evidence for the positive influence of children's participation in the arts on the development of crucial cognitive skills. The implications of this research suggest that integrating arts-based experiences into children's learning environments can support their academic achievement by enhancing critical thinking, creativity, and problem-solving abilities. Further longitudinal studies are recommended to investigate the mechanisms underlying the relationship between arts engagement and cognitive development.